Evaluation Of Priority Criteria For Selecting Subcontractors In Highway Construction Projects In Nusantara Capital City (Ikn) Project - Alekander, Rengki; Wirjodirdjo, Budisantoso (JURUSAN TEKNIK SIPIL, 2025)
The selection of appropriate subcontractors plays a critical role in the success of construction projects, particularly in strategic infrastructure projects such as Section 6B of the Highway Construction Project in Nusantara Capital City. This project experienced delays and cost deviations of 4.43% due to subcontractor selection based solely on two common criteria—experience and lowest price—while neglecting additional important criteria such as technical qualifications and managerial capabilities, which could mitigate project risks. This study aims to identify and analyze subcontractor selection criteria to enhance project success and reduce delays and cost overruns based on the experience and assessments of stakeholders. Previous research indicates that commonly used methods have not sufficiently addressed issues of delays and cost deviations. Therefore, this study explores more effective methods, employing the Delphi, DEMATEL, and ANP methodologies. The Delphi method, through three survey rounds, identified seven criteria and sub-criteria. DEMATEL was then applied to assess relationships among these criteria, identifying dominant causal or effect factors. Finally, the ANP method determined priority criteria and sub-criteria. The results revealed that Price held the highest priority weight (23%), followed by Quality (21%), Technical (18%), Delivery (13%), Organization (8%), and Internal (6.5%). Among sub-criteria, Bid Price had the highest weight (16%), followed by Standard Quality (8%) and others with similar significance